Money Politics and Violations of Voters’ Political Rights: An Analysis of Article 523 of Law No. 7 of 2017 on Elections - Temmy Fitriah Alfiany; Yenik Pujowati; Rani Eka Arini (West Science Law and Human Rights, 2026)
Money politics remains one of the most significant challenges threatening the integrity of democratic elections in Indonesia because it directly affects the independence and authenticity of voters’ political choices. Although elections are constitutionally guaranteed as a mechanism for exercising popular sovereignty, the practice of providing money or material benefits to influence voters continues to undermine the principles of free, honest, and fair elections. This study aims to analyze money politics as a violation of voters’ political rights and examine the legal effectiveness of Article 523 of Law Number 7 of 2017 concerning General Elections as an instrument for preventing and addressing electoral manipulation. This research employs a normative legal method using a statutory approach, conceptual approach, and analytical approach. The study examines primary legal materials, particularly the 1945 Constitution of the Republic of Indonesia and Law Number 7 of 2017 concerning General Elections, supported by secondary legal materials from legal literature and academic studies. The findings indicate that money politics constitutes a violation of political rights because it disrupts voter autonomy, creates unequal political competition, and prevents elections from reflecting the genuine will of citizens. Article 523 of Law Number 7 of 2017 provides an important legal framework by criminalizing the provision or promise of money and material benefits intended to influence voters. However, its implementation faces challenges, including difficulties in proving electoral crimes, limited enforcement mechanisms, and the persistence of transactional political culture. Therefore, strengthening election law enforcement, improving institutional capacity, and increasing political awareness are necessary to ensure effective protection of voters’ political rights and the realization of substantive democracy in Indonesia.